The Contribution of Stocked Trout to the Sport Fishery of Three Small Wisconsin Lakes - Jesien, Roman V (University of Wisconsin-Stevens Point, College of Natural Resources, 1977)
To assess the effectiveness of stocking catchable-size trout in spring, creel surveys were conducted on lakes that were stocked with fin-clipped trout: Sunset Lake, Portage County, 26 ha, received 103 rainbow trout (Salmo gairdneri) per ha; Thomas Lake, Portage County, 13 ha, received 183 rainbow trout per ha; lake. Dorothy, Oneida County, 39 ha, received 77 rainbow trout and 51 brook trout (Salvelinus fontilalis) per ha. Experimental electrofishing was carried out on Lakes Sunset and Thomas to gain information on non-trout species. Estimated percentages of stocked trout harvested the first month of the angling season at Sunset Lake in 1975 and 1976, Thomas Lake in 1976 and rainbow and brook trout in Lake Dorothy in 1976 were 46, 72, 62, 22, and 64, respectively. The estimated total harvest of stocked rainbow trout for the 1975 season in Sunset Lake was 48%, and few trout appeared to survive to the second year in any lake. Fishing pressure was also concentrated in the first two weeks of the season, 67S in the first month of the total 7906 angler hours in the 9 month season in 1975 and 85% of a two month total of 5836 angler-hrs in 1976 at Sunset Lake. Estimated percentages of stocked weight returned for the first month of the season at Sunset Lake in 1975 and 1976, Thomas Lake in 1976 and rainbow and brook trout in Lake Dorothy in 1976 were 47, 76, 113, 31, and 80, respectively. Trout were the most abundant species in the harvest during May on all lakes and also in June 1976 in Sunset Lake. The second most abundant species in the creel was white sucker in Sunset Lake and bluegill in Lakes Thomas and Dorothy. Mark/recapture population estimates from electrofishing of fish older than age one in Sunset Lake were 18 and 20 kg/ha of white sucker in 1975 and 1976 and 3.4, 3.7, and 27.6 kg/ha of yellow perch, largemouth bass, and cisco, respectively, in 1976. In general, the return of stocked trout to the creel, both numbers and weight, at the study lakes was above average compared to other lakes. Also, in general growth of trout in the study lakes was similar to that in other inland lakes in Wisconsin. However, growth rate was highest in Thomas Lake where non-bait food in trout was three times greater than in Sunset Lake, and as a result the weight of trout harvested exceeded the weight stocked (113%). In Sunset Lake 57% of the weight stocked was recovered during the 1975 - 76 season, but the following season 96% was recovered by the end of June. Results of other studies indicate that 1) stocking larger trout yields higher returns than stocking smaller trout, 2) stocked brook trout provide higher returns than rainbow trout, but when stocked at subcatchable-size, brown trout yield the highest returns of the three species, 3) returns are higher for rainbow trout stocked in summer and brook and brown trout in spring than in other seasons, 4) comparisons of various strains of stocked trout have been inconclusive. Warmwater species of fish support the sport fishery in Sunset Lake, and probably in the other lakes, from July through February. Growth of yellow perch, an apparently recent invader, in Sunset Lake was high in comparison to other waters. Growth of largemouth bass, bluegill, and cisco, and food habits of stocked trout largemouth bass, bluegill, yellow perch, cisco, and white sucker were similar to those characteristics in other waters.